AC susceptibility as a characterization tool for coated conductor tapes. (3rd October 2017) - Gömöry, F; Vojenčiak, M; Solovyov, M; Frolek, L; Šouc, J; Seiler, E; Bauer, M; Falter, M
Abstract: The measurement and analysis of magnetic AC susceptibility is a useful tool in the study of superconductor (SC) materials. Exposure of a sample to a magnetic field changing in time generates loops of electrical currents that are detectable in a contactless way with the help of a suitable pick-up system. In this paper the applicability of this technique in the characterization and quality control of coated conductor (CC) tapes is evaluated. First we recollect the essential results of the analytical theory derived for thin SC strips and their extrapolation to strips with finite thickness. From the analytical expressions one can see how the properties of CC tape that are important for application in electric power devices, namely its critical current and AC loss, can be deduced from AC susceptibility data in straightforward way. The main focus of our study is to investigate the influence that various cases of non-uniformities in SC layer exhibit on the magnetic properties examined in an AC regime. Numerical computations were used to explore the consequences of lateral variation in the critical current density. Predictions derived for some model cases were compared with experimental findings. A dedicated experiment was also carried out to demonstrate that a transverse scratch that would be detrimental for DC transport could sneak unobserved through the AC magnetic experiment on a long sample. Our study shows that the analysis of both parts of the complex magnetic susceptibility in place of a mere AC loss determination in a common AC magnetization experiment is worth the additional effort.